ORAL ENGLISH PROFICIENCY: OBSTACLES AND SOLUTION FOR UNIVERSITY STUDENTS ON MUHAMMADIYAH UNIVERSITY OF SURAKARTA - Muamaroh, Muamaroh (Universitas Muhammadiyah Surakarta, 2009)
The objectives of this study are to describe the obstacles in oral English proficiency and to describe the ways in overcoming the obstacles. The respondents wereuniversity students of English Department of Teacher Training and Education ofMuhammadiyah University of Surakarta Indonesia. The samples consist of 31 malestudents and 42 female students. The instruments used to collect were questionnaire,Â in depth interview and class observation. This study used qualitative descriptive analysis. The results showed that obstacles that came from cognitive factors were the lackÂ of vocabularies, grammar mastery, and pronunciation problems. From affective factors were anxiety, fear, shame, and lack of confidence. The obstacles in speakingÂ English came from the studentsâ negative perception that speaking English was difficult, and the studentsâ laziness, they rarely practiced speaking English and the environment was not conducive. The solutions to solve the problems in practicing speaking English, for male and female students were improving vocabularies regularly,Â practicing speaking English independently, listening Western songs, watching English movies, practicing speaking English with each other or foreigners, reading English novels, English newspapers or English magazines, taking English course, andÂ writing diary. The findings contribute to an understanding of obstacles and solutionsÂ of male and female students in speaking English in Indonesian context.Keywords: oral English proficiency, obstacle.